Atlas of the national parks - Waterman, Jonathan (National Geographic, 2019)
Presents a full-color guide to all of America's national parks organized by region. Includes a full examination the geology, tectonics, flora and fauna, archaeology, visitor experience, human impact, and extremes of the country as a whole before discussing each park individually. Each park entry contains key data, a description of the park's history, how humans interact with the land, and suggested exploration opportunities.